Views of Queen of Bohemia's Palace, or Craven House, in Drury Lane and Wych Street - Howlett, Bartholomew; Ravenhill (Tufts Archival Research Center, 2008)
With a plan of the site. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.